2014
DOI: 10.1603/en13223
|View full text |Cite
|
Sign up to set email alerts
|

Alate Trap-Based Assessment of Formosan Subterranean Termite (Isoptera: Rhinotermitidae) Dispersal Flight Phenology Associated With an Urbanized Barrier Island Ecosystem

Abstract: During 2009, 2010, and 2011, the reproductive dispersal flight phenology of Formosan subterranean termites (Coptotermes formosanus Shiraki) was assessed on Galveston Island, TX, via LED light-based termite alate traps. In all three years, traps were deployed at sampling sites before the initiation of C. formosanus dispersal flights, and retrieved weekly until the cessation flights. In total, 45, 102, and 90 traps were deployed during 2009, 2010, and 2011, respectively. In all years, C. formosanus flights began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…We obtained the same results using average or minimum temperature (GLMM; P < 0.001), but the AIC was smallest with maximum temperature. The observed relationship between the highest temperature and swarming events is consistent with field observations in other termite species (e.g., (Chouvenc et al, 2017; Puckett et al, 2014; Sugio et al, 2020)). Two of the seven colonies observed had the swarming event on the same day (colonies I and VII).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We obtained the same results using average or minimum temperature (GLMM; P < 0.001), but the AIC was smallest with maximum temperature. The observed relationship between the highest temperature and swarming events is consistent with field observations in other termite species (e.g., (Chouvenc et al, 2017; Puckett et al, 2014; Sugio et al, 2020)). Two of the seven colonies observed had the swarming event on the same day (colonies I and VII).…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have identified the environmental cues that elicit a swarming flight by social insects (Hölldobler and Wilson, 1990; Nutting, 1969). In termites, for example, high temperature is a good predicting factor of the occurrence of swarming flights in some species (Chouvenc et al, 2017; Puckett et al, 2014; Sugio et al, 2020), while rainfall and humidity are essential triggers for species especially in arid (Aihetasham and Akhtar, 2008) or tropical regions (Lucena et al, 2022; Mitchell, 2008; Neoh and Lee, 2009). The environmental cues are sometimes complex, where air temperature and relative humidity are not the only factors (Martius, 2003; Sands, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variability in the numbers of C. formosanus alates swarming at the same locations from year to year ( Osbrink et al. 2011 ; Puckett et al. 2014 ).…”
mentioning
confidence: 99%
“…2011 ). In Galveston, TX, significantly more alates were captured in 2009 than in 2010 and 2011 ( Puckett et al. 2014 ).…”
mentioning
confidence: 99%